Legal Implications of Private Credit Agreements Registered with a Notary on the Validity of Mortgage Guarantees in Banking Practices. - Wildani, Bella Rahmatika Sahda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study analyzes the legal implications of the use of private credit agreements registered with a notary on the validity of Mortgage guarantees in banking practices in Indonesia. Although the banking sector is highly dependent on collateral, often the principal credit agreement underlying the Mortgage is made privately and only legalized by a notary. The first problem formulation examines the legal status of private credit agreements registered with a notary. It was found that the deed remains a private deed. However, registration with a notary provides certainty of the date and signature, thereby increasing its formal evidentiary power. However, notary legalization does not guarantee the material truth of the agreement's contents, leaving the potential for disputes if the contents of the agreement are disputed. The second problem formulation discusses the legal implications of registering the deed on the validity of the Mortgage guarantee. Formally, this legalized deed is sufficient as a basis for the PPAT to issue a Deed of Granting Mortgage Rights (APHT). However, based on the principle of accession, if the principal credit agreement is proven to be legally flawed or void at a later date, the mortgage attached to it will also be void by law. This places a heavier burden of proof on the bank as the creditor in the event of a dispute regarding the validity of the agreement's contents. In conclusion, although registering a private credit agreement deed with a notary increases formal certainty, it does not completely eliminate legal risks related to the validity of the agreement's contents and its impact on the mortgage guarantee. Therefore, banking practices should prioritize the preparation of credit agreements in the form of authentic deeds before a notary to achieve maximum legal certainty and minimize the risk of disputes.